SELF-REPORTED ALCOHOL CONSUMPTION AND ASSOCIATION TO CARBOHYDRATE-DEFICIENT TRANSFERRIN AND GAMMA-GLUTAMYLTRANSFERASE IN A RANDOM SAMPLE OF THE GENERAL POPULATION IN THE REPUBLIC OF KARELIA, RUSSIA AND IN NORTH KARELIA, FINLAND - Laatikainen, Tiina; Alho, Hannu; Vartiainen, Erkki; Jousilahti, Pekka; Sillanaukee, Pekka; Puska, Pekka (Alcohol and Alcoholism, 2002)
— In the present study, alcohol consumption was estimated in a population survey in Pitkäranta in the Republic of Karelia, Russia (RUS) and in the neighbouring province of North Karelia in Finland (FIN) in the spring of 1997 in connection with the National FINRISK Study. Alcohol consumption was evaluated by self-report and by the biological markers carbohydrate-deficient transferrin (CDT) and gamma-glutamyltransferase (GGT). In RUS, elevated CDT values were observed in 36.6% of the men and 17.6% of the women. In FIN, the respective rates were 9.6% and 9.4%, which are similar to average European rates. The prevalence of elevated CDT values seen in RUS is the highest prevalence ever reported in general population surveys. However, the self-reported alcohol consumption was similar in the two regions. These results suggest that alcohol consumption especially in Russia may not be reliably estimated by self-reporting, and that alcohol consumption is relatively high, especially among men, in RUS.